Impact-resistant and wear-resistant mass concrete and application thereof
By spraying modified polyurea on the surface of large volume concrete, the problem of hydraulic water discharge buildings is easily damaged under the action of high-speed sand-containing water flow, and the effect of significantly improving impact and wear resistance is achieved, extending the service life of the building and reducing maintenance costs.
Patent Information
- Application Number
- CN202411915537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Hydraulic water discharge buildings are prone to wear and damage under the action of high-speed sandy water flow, resulting in peeling of surface materials and exposed reinforcement, affecting the safe operation of the building and consuming a lot of manpower and financial resources.
Spray or coat modified polyurea on the surface of large volume concrete. The modified polyurea is made of polymerization of amino components and isocyanate prepolymers to improve the impact, wear and seepage resistance of concrete.
The modified polyurea coating significantly improves the impact and wear resistance of large volume concrete, enhances its resistance to high-speed sandy water flow, extends the service life of the building, and reduces maintenance costs.
Smart Images

Figure CN119707399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to impact-resistant and wear-resistant large-volume concrete and application thereof. Background Art
[0002] Hydraulic spillway structures are hydraulic structures used in water conservancy projects to discharge floods or waterlogging that exceed the storage or bearing capacity of reservoirs, rivers, channels, and waterlogged areas, as well as to release water in reservoirs and channels for safety protection or inspection and maintenance. Their main function is to ensure the safety of water conservancy hubs and hydraulic structures and reduce the impact of flood disasters. For hydraulic spillway structures, the erosion and abrasion damage to the flow surface caused by high-speed sand-containing water flow is one of the common hazards. Nearly 70% of large concrete dams have erosion and abrasion damage during operation. Such damage will cause the surface material to peel off and the reinforcement to be exposed, affecting the normal operation of the spillway structure, and in severe cases, it will cause catastrophic accidents. Abrasion damage will not only affect the safe operation of hydraulic spillway structures, but repeated repairs of hydraulic spillway structures damaged by erosion and abrasion will also consume a lot of manpower and financial resources. In recent years, my country has vigorously developed the hydropower resources in the southwest. A number of large-scale water conservancy and hydropower projects have been built and are under construction, including Jinping, Longtan, Xiangjiaba, Xiluodu, Xiaowan, Wudongde, etc. The rivers have a large drop, high head, high water and sand content, and large single-width discharge, which puts higher requirements on the abrasion resistance of discharge structures. Therefore, the research on abrasion-resistant materials has always been the research focus of abrasion resistance of hydraulic discharge structures.
[0003] According to the different damage mechanisms, abrasion damage can be divided into abrasion damage, cavitation damage and scouring damage. During the operation of the discharge structure, various forms of damage often occur simultaneously and may promote each other. Therefore, the anti-abrasion material is required to have excellent comprehensive anti-abrasion ability. The selection of anti-abrasion materials with good performance has great engineering and economic significance for the safe service and operation of hydraulic discharge structures. The research on anti-abrasion materials has begun since the 1960s. In 1968, epoxy concrete and furan concrete were used to repair the bottom plate and apron of the sand flushing gate of Shimian Hydropower Station. In 1979, the Erjiang spillway of Gezhouba Project and other flow structures used polymer impregnation technology to strengthen the concrete surface and polymer impregnation repair of fine cracks on the dam surface. In the mid-1990s, China successfully developed polyurea technology and applied it to many water conservancy projects such as the volute of Heilongjiang Nierji Hydropower Station, Beijing Sanjiadian Weir, Guangdong Heshan Weir, and Shanxi Longkou Hydropower Station.
[0004] Polyurea is an elastomeric material with high strength and toughness. It has attracted people's attention due to its abrasion resistance, aging resistance, corrosion resistance, impact resistance and unique construction performance. In the mid-1990s, Professor Huang Weibo in China took the lead in successfully developing polyurea technology, which has been applied in many water conservancy and water transport projects with good results. Polyurea materials have excellent tolerance to factors such as natural light, freeze-thaw, and temperature changes. Its superelasticity gives the material excellent crack resistance, and has a good inhibitory effect on cracks and crack expansion on the concrete dam surface. However, the reaction rate of polyurea materials is relatively fast, and it is easy to form an excessively large molecular weight, resulting in poor fluidity of the material, which affects the processability of polyurea. At the same time, polyurea materials are used on the surface of hydraulic discharge structures, and the requirements for water resistance and abrasion resistance are relatively high. Summary of the invention
[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides impact-resistant and wear-resistant mass concrete, wherein modified polyurea is sprayed or coated on the surface of the mass concrete, thereby improving the impact resistance, wear resistance and impermeability of the mass concrete.
[0006] The technical solution for achieving the purpose of the present invention is as follows:
[0007] A large volume concrete that is impact-resistant and wear-resistant, comprising steel bars and concrete, wherein the mix ratio of the concrete is: coarse aggregate 1300-1500 kg / m 3 , Fine aggregate 600~800kg / m 3 , cement 100-200kg / m 3 , mineral admixture 40~100kg / m 3 , water reducing agent 1~10kg / m 3 , water 80~150kg / m 3 The outer surface of the mass concrete is covered with a modified polyurea having a thickness of 1 to 10 mm, wherein the modified polyurea is polymerized from an amino component and an isocyanate prepolymer, wherein the amino component comprises a fluorinated aminosiloxane and a maleate-substituted triamine in a molar ratio of (1 to 2): (8 to 9).
[0008] Specifically, the structural formula of the fluorinated aminosiloxane is shown in Formula 1, and the structural formula of the maleate-substituted triamine is shown in Formula 2:
[0009]
[0010] Where R1 is
[0011] R2 is at least one of CH3, CH2CH3, CH(CH3)2, and CH2CH2CH2CH3.
[0012] The molar ratio of the amino group of the amino component to the isocyanate group of the isocyanate prepolymer is 100:(101-110).
[0013] In a specific embodiment, the fluorinated aminosiloxane is prepared by reacting 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane with hexafluorobutyl methacrylate in a molar ratio of 1:(2.01-2.1) through Michael addition reaction under nitrogen atmosphere.
[0014] In a specific embodiment, the preparation method of the maleate-substituted triamine is as follows: under a nitrogen atmosphere, a triamine and a maleate in a molar ratio of 1:(3.01-3.1) are reacted by Michael addition reaction.
[0015] In a specific embodiment, the isocyanate prepolymer is a polymer of diisocyanate and polypropylene oxide, and the isocyanate group content of the isocyanate prepolymer is 12 to 18 mol%.
[0016] Specifically, the polyamine is at least one of tris(2-aminoethyl)amine and melamine.
[0017] The maleate is at least one of dimethyl maleate, diethyl maleate, diisopropyl maleate and dibutyl maleate.
[0018] The diisocyanate is at least one of isophorone diisocyanate, meta-xylylene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate and hexamethylene diisocyanate.
[0019] In a specific embodiment, the fine aggregate is natural river sand or machine-made sand, and the stone powder content of the natural river sand or machine-made sand is 11-16.6wt%. Preferably, the stone powder content of the natural river sand or machine-made sand is 12-15wt%. Further preferably, the stone powder content of the natural river sand or machine-made sand is 13wt-14wt%.
[0020] In a specific embodiment, the coarse aggregate is at least one of crushed stone or pebbles, and the particle size of the crushed stone or pebbles is 5-80 mm. More preferably, the coarse aggregate is obtained by three-graded crushed stone or pebbles with particle sizes of 5-20 mm, 20-40 mm, and 40-80 mm.
[0021] In a specific embodiment, the cement is at least one of ordinary Portland cement, low-heat Portland cement or medium-heat Portland cement, and the water-cement ratio is 0.34-0.46.
[0022] In a specific embodiment, the mineral admixture is at least one of fly ash, mineral powder, silica fume, and kaolin; preferably, the mineral admixture is fly ash and mineral powder.
[0023] In a specific embodiment, the method for preparing the mass concrete comprises the following steps:
[0024] (1) Tie the foundation slab and steel bars in the excavated foundation trench, support with concrete pads of the same strength, and install the formwork;
[0025] (2) Put coarse aggregate, fine aggregate, cement and mineral admixture into the mixing station, stir for 1 to 2 minutes, then add ice-water mixture, stir for 2 to 5 minutes, then add water reducer, and continue stirring until the ice is fully melted and the concrete outlet temperature is ≤16°C;
[0026] (3) Concrete is poured into the steel formwork in layers using a pump truck, with each layer of 30 to 50 cm evenly distributed. Concrete is vibrated using a φ50mm inserted manual vibrator until cement slurry appears on the surface of the concrete and no longer sinks and there is basically no bubbling on the surface;
[0027] (4) After vibrating and leveling, the concrete surface is covered with plastic film, and after hardening, the formwork is removed and the roughening is performed, and then standard curing is carried out for at least 28 days;
[0028] (5) The fluorinated aminosiloxane of the amino component, the maleate-substituted triamine and the isocyanate prepolymer are mixed on site and stirred for 4 to 6 minutes to obtain a modified polyurea, which is then sprayed on the surface of a dry and clean mass concrete with a thickness of 1 to 10 mm and air-dried for at least 24 hours.
[0029] Another object of the present invention is to protect the application of the mass concrete in ship locks, hydropower stations, and water-blocking and discharge buildings.
[0030] Beneficial Effects
[0031] The invention provides a kind of impact-resistant and wear-resistant mass concrete, which is prepared by spraying or coating modified polyurea on the surface of mass concrete, wherein the modified polyurea is polymerized by an amino component with an amino group and an isocyanate prepolymer with an isocyanate group, the fluorosilicone group can further improve the hydrophobicity and wear resistance of the polyurea coating, the hyperbranched polymerization method improves the fluidity of the polyurea polymer, makes the polyurea polymer easier to spray, and can form a cross-linked network structure after solidification, thereby improving its mechanical properties. In addition, in order to avoid the overly rapid and violent reaction of the amino group and the cyanate group, a fluorine-containing aminosiloxane with a secondary amine structure and a maleate are used to replace the triamine, and the isocyanate is prepared in the form of a prepolymer, thereby slowing down the curing time after the amino component and the isocyanate prepolymer are mixed, and the time difference requirement between the configuration and the spraying completion in the actual construction site is met. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the H-NMR spectrum of fluorinated aminosiloxane;
[0033] Figure 2 This is the H NMR spectrum of diethyl maleate substituted tris(2-aminoethyl)amine;
[0034] Figure 3 This is a comparison chart of Example 1 and Comparative Example 7 after the concrete abrasion resistance test using the rotary jet method. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0037] The raw materials used in the embodiments and comparative examples are described as follows:
[0038] Cement: Ordinary Portland cement, PO 42.5R, purchased from China Resources Cement;
[0039] Mineral admixture 1: mineral powder, S95 mineral powder, purchased from Yangchun New Steel Co., Ltd. of Xiangtan Steel Co., Ltd.;
[0040] Mineral admixture 2: fly ash, fineness (45um square hole sieve residue) is 21.8%, Guodian Shenzhen Energy Huayingshan Power Generation Co., Ltd.;
[0041] Fine aggregate 1: machine-made sand, with a stone powder content of 9.8wt%; from Liuzhou City, Guangxi;
[0042] Fine aggregate 2: machine-made sand, with a stone powder content of 13.2wt%; from Liuzhou City, Guangxi;
[0043] Fine aggregate 3: machine-made sand, with a stone powder content of 16.6wt%; from Liuzhou City, Guangxi;
[0044] Coarse aggregate: granite crushed stone, produced in Liuzhou City, Guangxi, with three grades of particle size: 5-20mm, 20-40mm, 40-80mm;
[0045] Water reducing agent: A series of polycarboxylic acid high-performance water reducers were purchased from Jiangsu Subote;
[0046] Ice-water mixture: The raw material is tap water, which meets the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006);
[0047] Hexafluorobutyl methacrylate: purity 96%, purchased from Guangzhou Hewei Pharmaceutical Technology Co., Ltd.;
[0048] 1,3-Bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane: purity 99%, purchased from Zhongshan Yuanda New Materials Co., Ltd.;
[0049] Triamine 1: tris(2-aminoethyl)amine, purity 97%, purchased from Guangzhou Hewei Pharmaceutical Technology Co., Ltd.;
[0050] Triamine 2: melamine: purity 99.5%, industrial grade, purchased from Guangzhou Haoyu International Trade Co., Ltd.;
[0051] Maleate: diethyl maleate, purity 99%, purchased from Guangzhou Shanghe Chemical Technology Co., Ltd.;
[0052] Diisocyanate: isophorone diisocyanate, purity 99%, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0053] Polypropylene oxide: average molecular weight 1000, product number 202320, purchased from Merck Life Sciences;
[0054] Hexamethylenediamine: analytical grade, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0055] HDI trimer: CAS: 3779-63-3, purchased from Guangdong Yunxing Biotechnology Co., Ltd.;
[0056] Polyurea: 9891, purchased from Wanhua Energy Saving Technology (Yantai) Co., Ltd.;
[0057] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0058] Preparation Example
[0059] Preparation Example 1
[0060] Modified polyurea 1: Homemade, the preparation method is as follows:
[0061] S1. Preparation of fluorinated aminosilane: Under nitrogen atmosphere, 1 mol of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane was placed in a reactor, and 2.1 mol of hexafluorobutyl methacrylate was added at a drop rate of 2 to 3 s / drop under stirring, and the temperature was raised to 40°C. After stirring at 40°C for 15 hours, the fluorinated aminosilane was filtered off under reduced pressure to obtain the fluorinated aminosilane; the structural formula of the fluorinated aminosilane is shown in Formula 1, and the H NMR spectrum is shown in Figure 1 As shown, the solvent is CDCl3;
[0062]
[0063] S2. Preparation of maleate-substituted triamine: Under nitrogen atmosphere, 1 mol of tris(2-aminoethyl)amine was placed in a reactor, heated to 40°C, and 3.1 mol of diethyl maleate was added at a drop rate of 2 to 3 s / drop under stirring, and the temperature was raised to 60°C. After stirring at 60°C for 36 hours, the reaction was filtered under reduced pressure to obtain a maleate-substituted triamine; the maleate-substituted triamine has a structural formula as shown
[0064] As shown in formula 2, the nuclear magnetic hydrogen spectrum is as follows Figure 2 As shown, the solvent is CDCl3;
[0065]
[0066] S3. Preparation of isocyanate prepolymer: Under a nitrogen atmosphere, 100 parts by weight of isophorone diisocyanate was added to a reactor, the temperature was raised to 50°C, 100 parts by weight of polypropylene oxide was added dropwise under stirring, and after the addition was completed, the temperature was raised to 75-80°C, and samples were taken every hour, and the isocyanate content was determined by the di-n-butylamine method. When the isocyanate content in the prepolymer was close to 15%, the reaction was terminated to obtain an isocyanate prepolymer;
[0067] S4. Before use, fluorine-containing aminosilane and maleate-substituted triamine are mixed in a molar ratio of 2:8 to obtain an amino component, which is mixed with the isocyanate prepolymer obtained in step S3 in a molar ratio of amino group to isocyanate group of 100:105 before use, and stirred for 4 minutes to obtain modified polyurea, which is sprayed onto the surface of large-volume concrete and cured naturally for 24 hours.
[0068] It should be noted that when the amino component and the isocyanate prepolymer are constructed on site, they are packaged in a configured ratio and no longer need to be weighed on site, and can be directly mixed and used.
[0069] Preparation Example 2
[0070] Modified polyurea 2: The preparation method is different from that of modified polyurea 1, except that the molar ratio of fluorinated aminosilane to maleate-substituted triamine is 1:9;
[0071] Preparation Example 3
[0072] Modified polyurea 3: The preparation method is different from that of modified polyurea 1, except that the tri(2-aminoethyl)amine in step S2 is replaced by melamine;
[0073] Preparation Example 4
[0074] Modified polyurea 4: The preparation method is different from that of modified polyurea 1, except that the molar ratio of fluorinated aminosilane to maleate-substituted triamine is 3:7;
[0075] Preparation Example 5
[0076] Modified polyurea 5: The preparation method is different from that of modified polyurea 1 in that the triamine is not replaced by maleate but is used directly;
[0077] Preparation Example 6
[0078] Modified polyurea 6: The preparation method is different from that of modified polyurea 1, except that the isocyanate prepolymer is replaced by HDI trimer;
[0079] Preparation Example 7
[0080] Modified polyurea 7: The preparation method is the same as that of modified polyurea 1, except that the tri(2-aminoethyl)amine in step S2 is replaced by hexamethylenediamine;
[0081] Preparation Example 8
[0082] Modified polyurea 8: The preparation method is different from that of modified polyurea 1, except that no fluorine-containing aminosilane is added;
[0083] The prepared modified polyurea was subjected to the following performance tests, and the results are shown in Table 1:
[0084] (1) Determination of coagulation time: At room temperature, the amino components of Preparation Examples 1 to 8 and the isocyanate prepolymer were mixed and the mixture was rapidly stirred while starting timing with a stopwatch. The time taken until the mixture stopped flowing was the coagulation time.
[0085] (2) Contact angle test: Mix the preparation examples 1 to 8 at room temperature and stir continuously. After stirring evenly, apply them on a glass slide. After solidification, cure them at room temperature for 7 days. Use water as the test liquid to test the contact angle data of the modified polyurea to water. Measure three sets of data for each sample and calculate the average value.
[0086] (3) Wear resistance test: Test conditions: load 500g, revolutions 500r, before fully cured, apply the preparation examples 1 to 8 on an iron sheet with the same length and width, wait for it to cure and dry, and then cure for 7 days. Before testing, weigh it on an analytical balance with an accuracy of 0.1mg, and then test it on a JM-IV abrasion tester. After the test, weigh the mass after the test on an analytical balance. The difference in mass before and after the test is the wear mass of the modified polyurea. For each modified polyurea test, three sets of data are tested and the average value is calculated.
[0087] Table 1 Test results of modified polyurea properties of preparation examples 1 to 8
[0088]
[0089]
[0090] From the test results of Preparation Examples 1, 2, 4, and 8, it can be seen that the introduction of fluorinated side chains and maleic acid esters not only improves the hydrophobicity and wear resistance of the polyurea coating, but also increases the reaction steric hindrance between amino groups and isocyanates, reduces their reaction activity, and greatly prolongs the coagulation time of polyurea, thus meeting the needs of actual construction.
[0091] It can be seen from the test results of Preparation Examples 1, 5, and 6 that when triamine and isocyanate are directly used for polymerization, due to the strong activity of primary amine, although isocyanate prepolymer is used to reduce the isocyanate group content, the reaction rate of triamine and isocyanate is still relatively fast, resulting in harsher use conditions. When isocyanate trimer is used instead of isocyanate prepolymer, although hyperbranched polyurea material can also be prepared, the isocyanate concentration is too high, the coagulation time is short, and the viscosity of the reaction system is high, so the apparent performance and physical and chemical properties of the prepared polyurea coating are poor.
[0092] It can be seen from the test results of Preparation Examples 1 and 7 that the hydrophobicity and wear resistance of linear polyurea are not as good as those of the hyperbranched polyurea material with a cross-linked network structure.
[0093] Examples and Comparative Examples
[0094] A large-volume concrete that is resistant to impact and wear refers to a thin-walled, large aspect ratio, and wide-section structure in a hub engineering structure. In a specific embodiment, the bottom plate size of the flood discharge gate is 35m×16.5m×2.6m, the gate pier casting block is 35m×1.75m×3m, the power station building bottom plate is 42m×29m×2.6m, the bottom plate size of the middle wall of the ship lock chamber is 32.8m×21.4m×1.5m, and the bottom plate size of the upper gate is 40m×23.5m×1.5m. The specific size can be adjusted according to the project situation or construction needs.
[0095] In a specific embodiment, the mass concrete is a laboratory specimen, and the specific size is a concrete structure of 1m×1m×1m.
[0096] In a specific embodiment, the method for preparing the mass concrete comprises the following steps:
[0097] Tie the foundation slab and steel bars in the excavated foundation trench, support with concrete pads of the same strength, and install the formwork;
[0098] Put coarse aggregate, fine aggregate, cement and mineral admixture into the mixing station, stir for 1 to 2 minutes, then add ice-water mixture, stir for 2 to 5 minutes, then add water reducer, continue stirring until the ice is fully melted and the concrete outlet temperature is ≤16℃;
[0099] Concrete is poured into the steel formwork in layers using a pump truck, with each layer of 30 to 50 cm evenly distributed. Concrete is vibrated using a φ50mm inserted manual vibrator until cement slurry appears on the surface of the concrete and it no longer sinks and there is basically no bubbling on the surface;
[0100] The vibrated and leveled concrete surface is covered with plastic film, and after hardening, the formwork is removed and the roughening is processed, and then the standard curing is carried out for at least 28 days; before spraying, the loose parts of the surface are removed to expose the solid base layer without moisture or water.
[0101] The amino component and the isocyanate prepolymer are mixed on site and stirred for 4 to 6 minutes to obtain the modified polyurea, which is then sprayed with a thickness of 5 mm on the surface of dry and clean mass concrete and air-dried for at least 24 hours.
[0102] The specific composition and proportion of the concrete are shown in Table 2.
[0103] Table 2 Specific composition and proportion of mass concrete (unit: kg / m 3 )
[0104]
[0105]
[0106] Performance Testing
[0107] The following tests were carried out on the concrete and the results are shown in Table 3.
[0108] (1) Wear rate and 28d abrasion resistance test: The wear rate and 28d abrasion resistance of concrete were tested in accordance with "4.20 Rotating jet method concrete abrasion resistance test" of DL / T 5150-2017 "Testing procedures for hydraulic concrete";
[0109] (2) 28d compressive strength: The 28d compressive strength was tested in accordance with "4.2 Concrete cube compressive strength test" of DL / T 5150-2017 "Testing Procedures for Hydraulic Concrete";
[0110] (3) 28d flexural strength: The 28d flexural strength was tested in accordance with "4.6 Concrete flexural test" of DL / T 5150-2017 "Testing procedures for hydraulic concrete";
[0111] (4) Impermeability test: The impermeability test of concrete is carried out in accordance with "4.24 Concrete impermeability test" of DL / T 5150-2017 "Testing procedures for hydraulic concrete";
[0112] Table 3 Performance test of mass concrete and its surface coating
[0113]
[0114]
[0115] It can be seen from the examples and comparative examples that the abrasion resistance, flexural strength and impermeability grade of the mass concrete coated with modified polyurea are significantly improved, but the compressive strength is slightly reduced.
[0116] From the performance test results of Examples 1, 5 and Comparative Example 1, it can be seen that the contribution of fluorinated aminosilicone to impact and wear resistance is best when the proportion of fluorinated aminosilicone is 10-20 mol%. When the content of fluorinated aminosilicone is increased to 30 mol%, phase separation is easily formed due to the incompatibility of fluorinated silicon and polyurea, which will lead to a decrease in the mechanical properties of the modified polyurea.
[0117] It can be seen from Examples 1, 6 and 7 that when the thickness of the modified polyurea coating is 4 to 6 mm, the overall impact resistance, wear resistance, compressive strength and flexural strength are best. When the coating thickness is higher, although the flexural strength is improved, the loss of compressive strength will also be more obvious.
[0118] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A large volume concrete that is impact-resistant and wear-resistant, characterized in that: It includes steel bars and concrete, the mix ratio of the concrete is: coarse aggregate 1300-1500kg / m 3 , Fine aggregate 600~800kg / m 3 , cement 100~200kg / m 3 , mineral admixture 40~100kg / m 3 , water reducing agent 1~10kg / m 3 , water 80~150kg / m 3 The outer surface of the mass concrete is covered with a modified polyurea having a thickness of 1 to 10 mm, wherein the modified polyurea is polymerized from an amino component and an isocyanate prepolymer, wherein the amino component comprises a fluorinated aminosiloxane and a maleate-substituted triamine in a molar ratio of (1 to 2): (8 to 9).
2. The mass concrete according to claim 1, characterized in that: The structural formula of the fluorinated aminosiloxane is shown in Formula 1, and the general structural formula of the maleate-substituted triamine is shown in Formula 2: Where R1 is R2 is at least one of CH3, CH2CH3, CH(CH3)2, and CH2CH2CH2CH3.
3. The mass concrete according to claim 1, characterized in that: The preparation method of the fluorine-containing aminosiloxane is as follows: in a nitrogen atmosphere, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and hexafluorobutyl methacrylate in a molar ratio of 1:(2.01-2.1) are reacted by Michael addition reaction to obtain the fluorine-containing aminosiloxane.
4. The mass concrete according to claim 1, characterized in that: The preparation method of the maleate-substituted triamine is as follows: in a nitrogen atmosphere, a triamine and a maleate in a molar ratio of 1:(3.01-3.1) are reacted by Michael addition reaction to obtain the triamine.
5. The mass concrete according to claim 1, characterized in that: The isocyanate prepolymer is a polymer of diisocyanate and polypropylene oxide, and the isocyanate content of the isocyanate prepolymer is 12-18 mol%.
6. The mass concrete according to claim 1, characterized in that: The polyamine is at least one of tris(2-aminoethyl)amine and melamine; the maleate is at least one of dimethyl maleate, diethyl maleate, diisopropyl maleate and dibutyl maleate; the diisocyanate is at least one of isophorone diisocyanate, meta-xylylene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate and hexamethylene diisocyanate.
7. The mass concrete according to claim 1, characterized in that: The fine aggregate is natural river sand or machine-made sand; the coarse aggregate is crushed stone or pebbles; the cement is ordinary Portland cement, low-heat Portland cement or medium-heat Portland cement; the mineral admixture is at least one of fly ash, mineral powder, silica fume and metakaolin.
8. The mass concrete according to claim 7, characterized in that: The stone powder content of the natural river sand or machine-made sand is 11-16.6wt%; the particle size of the crushed stone or pebble is 5-80mm; and the mineral admixtures are fly ash and mineral powder.
9. The mass concrete according to claim 1, characterized in that: The water-to-cement ratio is 0.34-0.
46.
10. Use of the mass concrete as claimed in any one of claims 1 to 9 in ship locks, hydropower stations and water retaining and discharge structures.
Citation Information
Patent Citations
Modified polyurea composite coating and preparation method thereof
CN111662622A
Preparation method of organic silicon modified polyurea
CN114276508A
Modified polyaspartic acid ester, preparation method and modified polyurea
CN116003784A
Polyurea composition having excellent retention performance of high durability for waterproofing surface of concrete structure and constructing method for waterproofing surface of concrete structure using the same
KR102505082B1